The role of Pediococcus pentosaceus IL13 in the fermentation of tuna waste, Euthynnus affinis - RAMADHAN, ZULFA AULIA; SUNARTI, TITI CANDRA; MERYANDINI, ANJA (Jurnal Natural, 2025)
Processing tuna fish (Euthynnus affinis) produces wastes like heads, tails, and viscera, which can pollute the environment. However, this waste is nutrient-rich and can serve as a source of peptones, antimicrobials, and antioxidants. Align with Sustainable Development Goals (SDGs) through the zero-waste concept, which emphasizes reducing waste production, this study aims to analyze the role of Pediococcus pentosaceusIL13 in the fermentation of tuna fish waste. The fermentation process was conducted over 30 days using two types of fermentation, spontaneously and with the addition of P. pentosaceus IL13 culture. Bacterial dynamics, pH, protein content, and amino acid concentration were monitored to assess fermentation performance. The study found a reduction in total bacteria and lactic acid bacteria (LAB) along with an increase in pH in both types of fermentation over time. Maximum protein and free amino acid levels were observed on day 10. In the spontaneous fermentation, protein concentrations were 5.590.15% in the liquid phase and 20.051.19% in the solid phase. In the fermentation with added culture, protein concentrations were 6.590.57% in the liquid phase and 19.560.00% in the solid phase. Amino acid concentrations were 4821.11149.3 ppm for spontaneous fermentation and 6271.11377.1 ppm for fermentation with culture. The protein hydrolysates in the liquid phase have antibacterial activity against S. typhi.